Evaluating the impact of a pre-rotation workshop on student preparation for clinical advanced pharmacy practice experiences - Medina MS; Stark JE; Vesta KS; Lockhart SM (Centro de Investigaciones y Publicaciones Farmaceuticas, 2008)
Objectives: This pilot study was designed to evaluate the impact of a pre-rotation workshop (PRW) on pharmacy students' clinical skills and preparation for clinical Advanced Pharmacy Practice Experiences (APPE) involving direct patient care. Methods: Randomized controlled trial of an educational intervention with Institutional Review Board approval. PRW activities designed to simulate rotation activities around five competencies, patient charts, medication histories, SOAP notes, patient presentations, and professionalism. Endpoints were evaluated using clinical rotation preceptors' evaluation of performance and students' performance on objective structured clinical exams (OSCE).Results: Eight fourth-year students and eight GPA matched controls (20% of the total class) were selected to voluntarily participate. The PRW demonstrated a positive impact on students' clinical skills and preparation for rotations by improving OSCE performance. However, no significant differences were found between groups when comparing preceptor evaluations of skills on rotations. These results are limited by the small sample size, potential OSCE "test-wiseness" effects, lack of OSCE evaluator blinding to study groups, potential case specificity effects due to the limited number of cases used on the OSCE and possible lack of sensitivity of the rotation evaluation tool to capture true differences among the experimental and control group participants.Conclusion: The PRW was successful at advancing students' clinical skills and preparation for rotations and may be considered as a tool to help bridge didactic to clinical experiences in the Pharm.D. curriculum.